The impact of COVID-19 and access to health services in the Hispanic/Mexican population living in the United States - Rangel Gómez, María Gudelia; Alcocer Varela, Jorge; Salazar Jiménez, Saúl; Olivares Marín, Leonardo; Rosales, Cecilia (Frontiers in Public Health, 2022)
Introduction The United States is home to 10.5 million undocumented immigrants, of which 5 out of 10 are Mexican or Central American. Their immigration status is an obstacle to secure employment that provides labor benefits such as sick leave and health insurance. Living through the global pandemic in the U.S. had a negative impact on this vulnerable population's mental and physical health. They avoided seeking primary or hospital care fearful that they were undocumented and uninsured. The services provided by the Ventanillas de Salud (VDS) “Health Windows” mitigated this pandemic's negative impact and have become an important source to support and increase access to health services among the immigrant community. Methods De-identified data from a database system called the Continuous Information System and Health Reports of Mexicans in the United States (SICRESAL-MX) to perform this secondary analysis. The descriptive analysis describes socio-demographic, epidemiological, and situational characteristics of COVID-19. Results Between January 2020 and July 2021, the VDS and UMS provided 11.5 million individual services to just over 4.3 million people. The main health conditions are overweight and obesity, high blood pressure and elevated cholesterol and glucose levels. Between March 2020 to July 2021 a total of 2,481,834 specific services related to COVID-19 were offered. Discussion The Mexican migrant community in the United States is in a vulnerable situation, largely due to its immigration status which limits their access to health and human services, including primary health care services. Many of them have suffered from chronic diseases since before the pandemic, generating difficulties in monitoring the ailments and exacerbating their conditions.